ANALISIS PERBEDAAN MOTIVASI DAN PRESTASI KERJA ANTARA KARYAWAN TETAP DAN KARYAWAN KONTRAK PADA PERUSAHAAN â€œKAMPOENG BRASCO FACTORY OUTLETâ€ CIPANAS CIANJUR JAWA BARAT - Arjak Prabowo; Ani Muttaqiyathun (Jurnal Fokus Manajemen Bisnis, 2012)
The purpose of this study was to determine the difference of the variable work motivation among permanent employees and contract employees (financial motivation and non financial motivation), and differences in job performance between among permanent employees and contract employees at the company Kampoeng Brasco Factory outlet cipanas, cianjur, west java. The population in this study were all permanent employees and contract employees Kampoeng Brasco Factory outlet cipanas, cianjur, west java respectively numbered 35 people. The sample selected for permanent employees using sampling methods saturated. And for contract employees using random sampling methods. This study used independent sample t-test. Current Research showed that motivation difference between permanent employees and contract employees. Research on work performance variables showed that performance difference between permanent employees and contract employees.